Development of a Flipbook-Assisted E-Module Integrating Problem-Based Learning to Enhance Students’ Conceptual Understanding - Siti Nurfadlah; Ila Rosmilawati; Indri Sari Utami (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop a flipbook-assisted e-module integrated with the Problem-Based Learning (PBL) model for the topic “This Is My Local Identity” in IPAS learning, and to evaluate its feasibility and effectiveness in enhancing elementary school students’ conceptual understanding. The study employed a Research and Development (R&D) method based on the ADDIE model and involved fourth-grade elementary school students. Data were collected through observation, interviews, questionnaires, and pretest–posttest assessments of conceptual understanding. The feasibility of the product was analyzed using Aiken’s V, while its effectiveness was measured using the N-gain test. The results showed that the developed e-module achieved an average Aiken’s V value of 0.80, indicating that it is valid and feasible in terms of both content and media aspects. Furthermore, the effectiveness analysis revealed an N-gain score of 0.67, categorized as moderate, indicating a significant improvement in students’ conceptual understanding after the implementation of the e-module. The integration of flipbook multimedia features with the PBL model created a more interactive, contextual, and meaningful learning environment. The visual and interactive elements embedded in the flipbook supported students in understanding abstract concepts of local identity through contextual problem orientation, exploratory activities, and collaborative discussions. This study contributes to the development of digital instructional media by providing empirical evidence that the integration of multimedia-based technology with student-centered learning models can enhance conceptual understanding in elementary education.